Occupational exposure to polychlorinated biphenyls in electrical workers. I. Environmental and blood polychlorinated biphenyls concentrations. Issue 1 (February 1981) - Maroni, M; Colombi, A; Cantoni, S; Ferioli, E; Foa, V
Abstract : Industrial exposure to polychlorinated biphenyls (PCBs) and internal dose were investigated in 80 worker exposed for many years to PCB mixtures with a 42% chlorine content (Pyralene 3010 and Apirolio). PCBs were determined by liquid gas chromatography on samples taken from workroom air, workroom surfaces and tools, the palms of the hand, and the blood of the workers. In the workroom air samples, PCB concentrations ranged from 48 to 275 micrograms/m3. All tested surfaces and tools were heavily contaminated, with a range from 0.2 to 159 micrograms PCBs per cm2 of surface. Considerable amounts of PCBs were detected on the palms of the hands of the workers (2-28 microgram/cm2 of skin surface). In blood, total PCB concentrations from 88 to 1319 micrograms/kg were observed: comparing the blood concentrations of low and high chlorine content biphenyls, a significant difference was found for the low-chlorinated biphenyl concentrations between workers currently exposed and workers exposed only in the past. In groups of workers who were homogeneous as regards work area and job, the PCB concentrations in the blood were closely correlated with the length of actual occupational exposure to these compounds. These findings led to the conclusion that absorption of PCBs in these workers had occurred mainly through the skin, therefore industrial preventive surveillance must take this route of exposure into account. Since blood PCB concentrations appear to be correlated with the length of exposure, PCB determination on whole blood may be used to monitor industrial and environmental exposure to PCBs.